Determination of the Regional Economy Leading Sectors in Indonesia - Amalia, Fitri (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2014)
Economic growth and its process are the main condition for the sustainability of the regional economic development. Because of the continuing population growth means economic needs also increase so that additional revenue required each year. This can be obtained by the increase in aggregate output (goods and services) or the Gross Regional Domestic Product (GRDP) each year. To carry out development with limited resources as a consequence should be focused to develop the sectors that provide great multiplier effect on other sectors or the whole economy. This research is focused to determine the regional leading sector of Bone Bolango as the information and considerations in planning economic development. Location Quotient (LQ) and Shift Share are tools of analysis. Location Quotient analysis indicates agriculture, manufacture, finance, leasing and corporate services are base sectors in the Bone Bolango district. Shift Share analysis indicates that the competitive sectors are finance, leasing and corporate services. The results of the analysis based on three analysis tools indicate that the leading sector with the criteria developed, base, and competitive is finance and services sector.